2022
DOI: 10.1002/ece3.9599
|View full text |Cite
|
Sign up to set email alerts
|

Can diet niche partitioning enhance sexual dimorphism?

Abstract: Classic evolutionary theory suggests that sexual dimorphism evolves primarily via sexual and fecundity selection. However, theory and evidence are beginning to accumulate suggesting that resource competition can drive the evolution of sexual dimorphism, via ecological character displacement between sexes. A key prediction of this hypothesis is that the extent of ecological divergence between sexes will be associated with the extent of sexual dimorphism. As the stable isotope ratios of animal tissues provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 199 publications
0
0
0
Order By: Relevance
“…For example, a study on lynx in Norway ( Lynx lynx ) showed that females with kittens had higher roe deer ( Capreolus capreolus ) kill rates compared to solitary females, likely linked to increased energetic demands (Nilsen et al., 2009 ). However, dietary differences between male and female carnivores are typically attributed to sexual size dimorphism (Bauld et al., 2022 ), where larger males are able to kill larger prey (Magnusdottir et al., 2012 ; Voigt et al., 2018 ). Yet we found that male and female coyote diets were quite similar across seasons, perhaps because males in our population are only ~2 kg heavier than females (on average).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on lynx in Norway ( Lynx lynx ) showed that females with kittens had higher roe deer ( Capreolus capreolus ) kill rates compared to solitary females, likely linked to increased energetic demands (Nilsen et al., 2009 ). However, dietary differences between male and female carnivores are typically attributed to sexual size dimorphism (Bauld et al., 2022 ), where larger males are able to kill larger prey (Magnusdottir et al., 2012 ; Voigt et al., 2018 ). Yet we found that male and female coyote diets were quite similar across seasons, perhaps because males in our population are only ~2 kg heavier than females (on average).…”
Section: Discussionmentioning
confidence: 99%
“…Historically the direction of SSD has been attributed to the balance of sexual selection for increased male size and fecundity selection for increased female size ( Fairbairn et al. 2007 ), although the role of ecological selection in generating SSD is increasingly being recognized ( Shine 1989 ; Mysterud 2000 ; Bauld et al. 2022 ; Bravo et al.…”
Section: Introductionmentioning
confidence: 99%